Evaluation of the Effectiveness and Adaptability of a Composite Water Control Process for Horizontal Wells in Deepwater Gas Reservoirs - Wang, Dianju; Li, Yihe; Ma, Lan; Yu, Fahao; Liu, Shufen; Qi, Tong; Jiang, Siyuan (Frontiers in Earth Science, 2022)
Deepwater gas fields have high bottom water energy and a high risk of seeing water. Higher requirements are put forward for the water control process to control the water effect. This article is based on the actual background and well design of the X gas field in the South China Sea and on three sets of physical simulation experiments and three sets of numerical simulation experiments. An analysis and comparison of the water control effect of a combination of continuous packer, continuous packer and variable density screen tube, and their adaptability evaluation in deepwater gas reservoirs were performed. The results obtained from the numerical and physical simulations are consistent. The experimental results show that the water control process of a continuous packer is mainly based on the water-seeing and water-blocking ability. It is less capable of extending the time to produce water in the horizontal section. However, its water-blocking ability is strong and is able to seal the water spot quickly. It extends the total production time by 12.29% and increases the total gas production by 5.96%; the combined water control process of the continuous packer and variable density screen tube can effectively play their respective advantages of water control. The combination of the continuous packer and variable density screen tube can effectively be advantageous of their respective water control processes, enabling the gas–water interface to advance in a balanced manner, extending the water-free gas recovery period by 11.61%, extending the total gas production time by 15.76%, and increasing the total gas production volume by 13.75%. Both water control processes have good applicability in deepwater gas fields and have certain sand control capability. It is conducive to the one-time completion operation for the commissioning of deepwater gas fields.